2022
DOI: 10.1371/journal.pone.0269995
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hashimoto thyroiditis and clinical outcomes of papillary thyroid carcinoma: A meta-analysis

Abstract: Objective To assess association between Hashimoto thyroiditis (HT) and clinical outcomes of papillary thyroid carcinoma (PTC). Methods Databases including Pubmed, Embase, Cochrane Library, and Web of Science were searched. Weighed mean differences (WMDs) and odds ratios (ORs) were used to evaluate association between HT and clinical outcomes of PTC, and the effect size was represented by 95% confidence intervals (CIs). Heterogeneity test was performed for each indicator. If the heterogeneity statistic I2≥50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 79 publications
4
7
0
1
Order By: Relevance
“…Additionally, certain aggressive features such as multifocality, extrathyroidal extension, and taller-than-wide nodules were no longer identified as independent risk factors in HT PTCs. These findings align with previous research ( Lee et al, 2013 ; Moon et al, 2018 ; Tang, Pan & Peng, 2022 ; Xu et al, 2021 ) and may suggest a protective effect of HT, reducing the invasiveness of PTC. Overall, the results of this study provide insights into the unique factors associated with CLNM in HT PTCs and highlight the importance of considering HT status when predicting CLNM in PTC patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, certain aggressive features such as multifocality, extrathyroidal extension, and taller-than-wide nodules were no longer identified as independent risk factors in HT PTCs. These findings align with previous research ( Lee et al, 2013 ; Moon et al, 2018 ; Tang, Pan & Peng, 2022 ; Xu et al, 2021 ) and may suggest a protective effect of HT, reducing the invasiveness of PTC. Overall, the results of this study provide insights into the unique factors associated with CLNM in HT PTCs and highlight the importance of considering HT status when predicting CLNM in PTC patients.…”
Section: Discussionsupporting
confidence: 92%
“…This not only affects the accuracy of ultrasound diagnosis but also has implications for surgical decision-making. However, most previous studies have only considered HT as a general factor predicting CLNM in PTC, without conducting a detailed analysis of the specific clinical and ultrasound factors that impact CLNM in HT PTCs ( Lee et al, 2013 ; Moon et al, 2018 ; Tang, Pan & Peng, 2022 ; Xu et al, 2021 ). Therefore, there is a need for comprehensive research focusing on the specific factors that influence CLNM in HT PTCs, in order to improve diagnostic accuracy and assist clinicians in making informed decisions regarding the extent of surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, HT brings a chronic inflammatory condition that awakens an immune response leading to a continuous damage of surrounding stromal cells, leading to an inappropriate cell proliferation and thus increasing the risk of neoplastic transformation [ 46 ]. On the opposite, it was reported that PTC patients with HT may have favorable clinicopathologic characteristics compared to PTCs without HT [ 47 ]. This inconsistency may result from low mortality rate associated with PTC and the protective effect of HT not being independent of tumor characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that thyroid autoantibodies present in patients with AIT may possibly also attack malignant thyrocytes, and thus contribute to a better prognosis. There are data on smaller tumour size, lower incidence of metastases, lower risk of disease persistence in PTC in the fi eld of AIT (20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic infl ammation can cause carcinogenesis by promoting genomic instability. Molecular studies have shown that thyrocytes can induce COX-2 and produce interleukin-6 under the infl uence of interleukin-1β (IL-1β) and tumour necrosis factor-α (TNF-α) (26). Increased COX-2 expression is known to be associated with carcinogenesis of various tumours by inhibiting apoptosis and promoting angiogenesis.…”
Section: ) Ptc Arises Based On or Is At Least Supported By The Pre-ex...mentioning
confidence: 99%